Weak utopianism in education - Murphy, Michael P. A., author.
1 online resource (xviii, 90 pages).
Keywords: In the light of the structural dangers of revolutionary change highlighted in the political theory of Giorgio Agamben, this book joins a lively debate in philosophy of education on weak utopianism as an approach that foregrounds and respects the educational potentiality of teachers and students. Utopian moves in education call for revolutionary changes in pedagogical practice in pursuit of a particular vision of the good. Whether grounded in emancipatory politics, technological enthusiasm, or another social movement, utopian moves are seductive in their promise of a better alternative. Weak Utopianism in Education draws together philosophy of education, political theory, scholarship of teaching and learning research, and utopian thought to advocate for a modest and humble approach to change. The theoretical foundation of weak utopianism opens space for educator's personal convictions and teaching philosophies to tinker with their own pedagogical practices. The book creates a common conceptual meeting ground for philosophers and practitioners in education.